2018
DOI: 10.4274/tjod.65299
|View full text |Cite
|
Sign up to set email alerts
|

Maternal platelet-to-lymphocyte ratio at delivery can predict poor neonatal outcome in preterm births

Abstract: Objective:To determine the role of the platelet-to-lymphocyte ratio (PLR) in predicting poor neonatal outcome among preterm births (PTB).Materials and Methods:The medical records of 439 PTBs and 200 normal pregnancies were reviewed retrospectively using some personal and obstetric data, as well as complete blood count reports.Results:There were significantly poor neonatal outcomes among PTBs in regard to birth weight, APGAR score, morbidity, and mortality. There were significantly poor outcomes for preterm neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…On the contrary, in our pre-eclamptic population, we found that low PLR was correlated with low birth weight, i.e. a poor pregnancy outcome, what has already been described in preterm births of any etiology [43]. The negative correlation between PLR and pre-eclampsia severity noted in some studies [19,20] is also concordant with our findings and plaids for a pejorative value of a low PLR at pre-eclampsia diagnosis or at delivery in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, in our pre-eclamptic population, we found that low PLR was correlated with low birth weight, i.e. a poor pregnancy outcome, what has already been described in preterm births of any etiology [43]. The negative correlation between PLR and pre-eclampsia severity noted in some studies [19,20] is also concordant with our findings and plaids for a pejorative value of a low PLR at pre-eclampsia diagnosis or at delivery in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…No statistically significant difference (p≥0.05) in the mean of gravida, para, and gestational age between cases and controls. These findings were consistent with the Turkish study done by Jaffar et al 11 The socio-economic status of cases and controls were matched each other (Table 3). Most of the patients were in the lower middle-income group.…”
Section: Discussionsupporting
confidence: 91%
“…Complete blood counts Sultana N et al Int J Reprod Contracept Obstet Gynecol. 2023 Nov;12 (11):3353-3357 were analyzed using a Coulter LH 780 Hematology Analyzer (Beckman Coulter Ireland INC, Mervue, Galway, Ireland). The platelet-to-lymphocyte ratio (PLR) was calculated by dividing the platelet count by the lymphocyte count.…”
Section: Study Proceduresmentioning
confidence: 99%
“…This variability can be attributed to obstetric conditions (PPROM, preeclampsia, and FGR), and maternal or fetal origin of blood parameters. In a study in which preeclampsia cases were not excluded, it was found that the increase in PLR was associated with low Apgar scores, intraventricular hemorrhage, sepsis, perinatal death, and respiratory distress, and a PLR > 80 can yield poor neonatal outcomes [33]. In another study comparing the Apgar scores at the 1 st and the 5 th minute in hypertensive and normotensive pregnant women with fetal NLR and PLR values, the platelet count was found to be low in infants of hypertensive mothers, and low PLR values were associated with a low Apgar score.…”
Section: Discussionmentioning
confidence: 99%